"Not Tonight, Honey:" Reasons Couples Do Not Engage in Sex and Their Impact on Satisfaction and Desire. Issue 3 (13th January 2020) - Mark, Kristen P.; Vowels, Laura M.; Leistner, Christine E.
Abstract: Introduction: Sexual activity is an important aspect of most romantic relationships. However, many couples report declines in sexual activity over time and report many reasons for not engaging in sexual activity on a daily basis. Aim: To investigate the reasons for not engaging in sexual activity in couples over a month and whether these reasons are associated with sexual and relationship satisfaction and sexual desire. Methods: We collected 30-day daily electronic report data from 174 individuals (87 mixed-sex couples). The responses between men and women were analyzed using chi-squared tests, and we used multilevel modeling to examine the association between the reasons and satisfaction and desire. Main Outcome Measure: The main outcome measure includes daily sexual satisfaction, relationship satisfaction, and sexual desire. Daily reported reasons for not engaging in sexual activity are categorized into joint reason, self-based reason, partner-based reason, and other reasons. Results: Men and women were equally likely to endorse joint reasons for not engaging in sexual activity (eg, "It just didn't happen"), whereas women were more likely to endorse self-based reasons (eg "I wasn't in the mood") and men partner–based reasons (eg "My partner was tired"). The reasons for not engaging in sexual activity were associated with daily sexual and relationship satisfaction and daily sexual desire. Higher baseline sexual desire was associated with a greater likelihood of endorsing partner-related reasons and smaller likelihood of endorsing self-related reasons. Higher baseline sexual satisfaction was associated with a decreased likelihood of reporting partner-based reasons, and higher baseline relationship satisfaction was associated with an increased likelihood of reporting joint reasons. Some of the other associations were significant only for men or women. Clinical Implications: Results inform couples' therapy and other clinical interventions and highlight the importance of addressing the reasons for not engaging in sexual activity to find ways of mitigating some of these reasons. Strength & Limitations: The study was the first to date to address reasons for not engaging in sexual activity in a sample of couples in an experience-sampling study. However, our scope was limited to mixed-sex couples who were primarily white and heterosexual, and we only addressed reasons for not engaging in partnered sex (not solitary sex). Conclusion: The reasons for not engaging in sexual activity seem different for men and women and are associated with sexual and relationship satisfaction and sexual desire, and this link appears to be bidirectional.